Analisis Casing Wear Ring Load Cycle Fatigue pada Sistem Kerja Pompa Sentrifugal ETA-N 100x80-200 di Bengkel Mekanik PEM Akamigas - Susilo Handoko; Muhammad Dhendy Sao Sao (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to analyze casing wear ring load cycle fatigue on the working system of eta-n 100x80-200 centrifugal pump at the akamigas mechanical workshop. This research method uses the step method. Simulation results using ANSYS 2024 software , obtained wear ring wear deformation of 0.378885 mm (average) and 0.3762455 mm (maximum) with wear ring clearance 0.38 mm. The comparison results of wear ring wear are less than the maximum wear ring tolerance, and wear ring wear is more than the minimum wear ring tolerance, so the results obtained still meet the tolerance standards. Simulation results of wear rings that are given 2x loading from the initial load